Mature dendritic cells correlate with favorable immune infiltrate and improved prognosis in ovarian carcinoma patients. Issue 1 (4th December 2018) - Truxova, Iva; Kasikova, Lenka; Hensler, Michal; Skapa, Petr; Laco, Jan; Pecen, Ladislav; Belicova, Lucie; Praznovec, Ivan; Halaska, Michael J.; Brtnicky, Tomas; Salkova, Eva; Rob, Lukas; et al.
Abstract : A high density of tumor-infiltrating CD8 + T cells and CD20 + B cells correlates with prolonged survival in patients with a wide variety of human cancers, including high-grade serous ovarian carcinoma (HGSC). However, the potential impact of mature dendritic cells (DCs) in shaping the immune contexture of HGSC, their role in the establishment of T cell-dependent antitumor immunity, and their potential prognostic value for HGSC patients remain unclear. We harnessed immunohistochemical tests and biomolecular analyses to demonstrate that a high density of tumor-infiltrating DC-LAMP + DCs is robustly associated with an immune contexture characterized by TH 1 polarization and cytotoxic activity. We showed that both mature DCs and CD20 + B cells play a critical role in the generation of a clinically-favorable cytotoxic immune response in HGSC microenvironment. In line with this notion, robust tumor infiltration by both DC-LAMP + DCs and CD20 + B cells was associated with most favorable overall survival in two independent cohorts of chemotherapy-naïve HGSC patients. Our findings suggest that the presence of mature, DC-LAMP + DCs in the tumor microenvironment may represent a novel, powerful prognostic biomarker for HGSC patients that reflects the activation of clinically-relevant anticancer immunity.